Human perception guided model simplification - Seenivasan Sashwath Ravilla (Nanyang Technological University, 2023)
This project aims to create an efficient 3D model simplification algorithm that is guided by human perception by combining Quadric Error Metrics (QEM) and Mesh Saliency. The proposed solution consists of two components: the application that loads and displays wavefront .obj files, and the algorithm that performs QEM simplification guided by saliency. The first component is essential to visualize the original and simplified versions of 3D models. The application is user-friendly, allowing the user to rotate, zoom, and pan the model. The second component, which is the algorithm, is the heart of the project. Beginning by implementing the QEM algorithm, Mesh Saliency will guide the simplification process by preserving the most visually significant parts of the 3D model. This report will provide a detailed account of the steps taken to develop the application and the algorithm, the challenges faced, and the results of the experiments.